2023
DOI: 10.1080/21642850.2022.2163248
|View full text |Cite
|
Sign up to set email alerts
|

Job stress and work from home during the COVID-19 pandemic among Japanese workers: a prospective cohort study

Abstract: Objectives The work style reforms and the coronavirus disease pandemic in Japan have prompted efforts toward teleworking, mainly work from home (WFH). This study aimed to prospectively evaluate the impact of WFH on job stress among Japanese workers. Methods This online survey-based prospective cohort study was conducted from December 2020 (baseline) to December 2021 (1-year follow-up) using self-administered questionnaires. At baseline, 27,036 participants completed the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…In some instances, remote work has been reported to increase workers’ productivity and be associated with better mental health 17 . However, current occupational health research has focused on the fact that social support from coworkers tends to decrease among remote workers, resulting in occupational distress 13 15 , 18 . During the present study period, when remote work had rapidly spread in its early stage in Japan, younger managers and professionals may have faced increased workloads without adequate social support, given that remote work was a new working style that was not experienced previously.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In some instances, remote work has been reported to increase workers’ productivity and be associated with better mental health 17 . However, current occupational health research has focused on the fact that social support from coworkers tends to decrease among remote workers, resulting in occupational distress 13 15 , 18 . During the present study period, when remote work had rapidly spread in its early stage in Japan, younger managers and professionals may have faced increased workloads without adequate social support, given that remote work was a new working style that was not experienced previously.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the prominence of remote work, particularly during the coronavirus disease 2019 (COVID-19) pandemic, has been a focus area in terms of occupational health 12 . Recent studies have revealed the psychological distress associated with remote work 13 15 . However, the impact of this trend on occupational CHD disparities remains unexplored.…”
Section: Introductionmentioning
confidence: 99%